Respuesta :
Hello there ^_ ^
6(x - 2) = 4
6x - 12 = 4
6x = 4 + 12
6x = 16
x = 16/6
x = 2.67
6(x - 2) = 4
6x - 12 = 4
6x = 4 + 12
6x = 16
x = 16/6
x = 2.67
6(x-2)=4
First you need to distribute, so multiply the 6 by both variables in the parentheses.
6*x-6*2=4
6x-12=4
Then add 12 to each side (The 12's will cancel each other out)
6x=16
Divide 6 by each side.
6x/6=16/6
x=2.67
Hope it helps!
First you need to distribute, so multiply the 6 by both variables in the parentheses.
6*x-6*2=4
6x-12=4
Then add 12 to each side (The 12's will cancel each other out)
6x=16
Divide 6 by each side.
6x/6=16/6
x=2.67
Hope it helps!